Technological importance of nitrogenic compounds in barley and malt. - J. PROKEŠ (Kvasný průmysl, 2000)
From the brewery point of view, nitrogen is one of the most significant components of barley. The article sums up the most meaningful pieces of knowledge the forms of abundance of nitrogen in barley, its influence on the quality of barley at of the produced malt. The article contains as well the principles for elaboration of barley with higher protein content. A marginal attention is given to the influence of malt on the quality and the sensoric stability of beer.From the brewery point of view, nitrogen is one of the most significant components of barley. The article sums up the most meaningful pieces of knowledge the forms of abundance of nitrogen in barley, its influence on the quality of barley at of the produced malt. The article contains as well the principles for elaboration of barley with higher protein content. A marginal attention is given to the influence of malt on the quality and the sensoric stability of beer.